Tratamento à base de zircônia aplicado sobre aços galvanizados como alternativa ao processo de fosfatização - Camilo Sanchez Velasquez (2017)
The present work makes a comparative evaluation of the corrosion resistance for galvanized steels treated with phosphate and zirconium conversion coatings. The anti-corrosion performance was studied using Electrochemical Impedance Spectroscopy (EIS) and accelerated corrosion tests. The samples characterization was performed using Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). Finally, the porosity for the conversion coatings was evaluated by Electrochemical Impedance Spectroscopy and Tafel analysis. Interpretation of the results suggests that zirconium conversion coatings did not improve the corrosion performance of phosphate coatings. The nature of the deposited layer is not continuous and did not cover the entire surface, this means that oxidizing agents can easily corrode the substrate as it penetrates through the defects of the coating.